Kebijakan Asesmen Nasional Berbasis Komputer pada Sekolah Luar Biasa - Yeny Rahmawati Priyanti (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The background of this research is that the National Assessment (AN) has been officially implemented by the Ministry of Education and Culture, which means that the National Examination (UN) is no longer enforced. The purpose of this research is to find out the national assessment policies applied to special schools. This research tries to focus on the policies applied by schools related to the implementation of the computer-based national assessment, besides that this research will also find out whether there are obstacles or obstacles in the implementation and implementation of the computer-based national assessment for students and teachers. If there are indeed obstacles, this research also tries to find the right solution in handling this so that the computer-based national assessment in this special school can be applied like other schools. The research method used is descriptive qualitative research using a case study, where researchers will use several research sources that have existed before to serve as a reference in the analysis that will be carried out in this study. Based on the results of research that has been carried out by conducting an analysis based on case studies on existing research sources, information is obtained that the implementation of the computer-based national assessment policy in several special schools has been carried out according to regulations from the Ministry of Education. However, the application and implementation of these policies naturally experienced several obstacles and obstacles. These obstacles and obstacles stem from teachers and students who cannot operate computers, as well as the lack of computer facilities in schools.